Effect of obesity in pregnancy: implications for maternal and fetal health - Bajaj, Gaurav; Davu, Gayathri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Obesity during pregnancy poses noteworthy threats to maternal and fetal health. This investigation looks to probe maternal obesity’s implications on pregnancy outcomes and neonatal health. This study employed a qualitative methodology utilizing secondary data analysis of recent literature to explore the associations between maternal obesity and pregnancy outcomes. Secondary data from 2017 to 2024 were gathered from peer-reviewed journals, databases, and reports published focusing on clinical characteristics and health parameters related to maternal obesity. Only studies providing detailed information on these factors were included. Clinical characteristics such as age distribution, gravidity, parity, and childhood obesity background significantly influenced pregnancy outcomes among obese women. A significant portion of the pregnant women with obesity, over half, were within the age range of 25-30 years, and a notable number had experienced obesity during their childhood. Additionally, obesity during pregnancy significantly impacted various health parameters compared to normal weight, including prepregnant BMI, maternal weight, and incidence of chronic conditions such as hypertension. Maternal obesity correlated strongly with adverse pregnancy outcomes, particularly preeclampsia and rectovaginal group B streptococcus infection. Similarly, adverse neonatal health outcomes were significantly associated with maternal obesity, including fetal macrosomia and neonatal intensive care unit (NICU) admission. Maternal obesity is linked with adverse pregnancy and neonatal outcomes, highlighting the prominence of managing maternal weight to boost maternal and fetal health. These discoveries underscore the necessity for targeted interventions and management strategies to mitigate the risks linked with obesity during pregnancy.